2020
DOI: 10.3390/coatings10090889
|View full text |Cite
|
Sign up to set email alerts
|

Thin Niobium and Niobium Nitride PVD Coatings on AISI 304 Stainless Steel as Bipolar Plates for PEMFCs

Abstract: In this paper, Nb, NbN, and Nb/NbN thin films were successfully deposited on AISI 304 stainless steel (304 SS) as the bipolar plate (BPP) for proton-exchange membrane fuel cell (PEMFC) by employing a radio-frequency (RF) magnetron sputtering system. Corrosion assessments in simulated PEMFC operating conditions (1 M H2SO4 + 2 mg/kg HF, 70 °C) revealed that the Nb and NbN coatings significantly improved the corrosion resistance of the 304 SS substrates. The Nb and NbN deposited samples at 350 °C exhibited superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Moreover, we have also demonstrated that Pt can be successfully replaced with corrosion resistant and highly conductive coatings of Nb [ 28 ]. Similarly, Nb and Nb/Ti coatings have also been used for corrosion protection of stainless-steel bipolar plates in PEM fuel cells [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we have also demonstrated that Pt can be successfully replaced with corrosion resistant and highly conductive coatings of Nb [ 28 ]. Similarly, Nb and Nb/Ti coatings have also been used for corrosion protection of stainless-steel bipolar plates in PEM fuel cells [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…NbN, being an excellent superconductor, is considered as one of the most commonly preferred materials in the electronic industry. [203][204][205][206][207][208] NbN can be used in diversified areas such as biomedical, [196,209,210] fuel cells, [211,212] cutting tools, [213] optical industry, [214,215] diffusion barriers, [197] thermometry, [216,217] supercapacitors, [218] cryogenics, [219,220] etc. Nonetheless, it can also be considered as a nonconventional material for cutting tool protective coatings due to its better combined thermal and mechanical properties than TiN.…”
Section: Applications Of Nbn Thin Filmsmentioning
confidence: 99%
“…Various surface modification techniques, including nitriding, cladding, and coating, have been applied to protect the surface of bipolar plates [ 8 , 9 , 10 , 11 , 12 ]. The nitriding process is known to be a useful method to improve the mechanical properties and corrosion resistivity of steels.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a modification process that operates under low temperature is needed to prevent the above problems. The coating process, in particular physical vapor deposition, could be promising due to its ready controlling of the thickness and uniformity of the protecting layer without a high treatment temperature [ 11 , 12 , 13 ]. As a protecting material, pure niobium (Nb) possesses excellent chemical stability and corrosion resistance in an acidic environment with higher electric conductivity.…”
Section: Introductionmentioning
confidence: 99%